(untitled) (Research, Society and Development, 2021)
Aim: The aim of this study will be to perform respiratory physiotherapy on patients with sleep bruxism and associated respiratory events (apnea and hypopnea). Methodology: The study will be a randomized, controlled, double-blind, clinical trial with a sample of individuals with sleep bruxism and associated respiratory events. Respiratory (inspiratory and/or expiratory) physiotherapy will be performed using the THRESHOLD IMT and PEP and the results will be compared to a placebo group. Discussion: Regarding respiratory events, there is a broad variety of possible treatments for sleep apnea depending on the physiopathology, severity and patient preference, with CPAP considered the gold standard. However, data on CPAP are inconsistent, with adherence to therapy reported to be between 45 and 89%. Thus, other forms of treatment are proposed, including respiratory training. Understanding obstructive sleep apnea syndrome as the loss of the dilation strength of the pharynx and the inability to maintain the path open for air, respiratory muscle training could assist in increasing dilation strength, enabling the passage of air during sleep. Taking into consideration that sleep bruxism may be associated with events of apnea and hypopnea, the intervention to treat obstructive respiratory events related to sleep may have a positive impact on events related to sleep bruxism (rhythmic activity of the masticatory muscles). To determine this, we will measure the apnea/hypopnea index (AHI) and number of contractions of the masseter muscle (characteristic of the activity of bruxism) before and after the intervention using polysomnography. Trial registration: The trial was registered with the REBEC platform: RBR-9F6JKM (ensaiosclinicos.gov.br).